WEB SERVICE FOR SUPPORTING OF WEBSITE PERFORMANCE - Sinta Tri Pamungkas; Agus Basukesti; Dwi Nugraheny (Compiler, 2012)
The growth of the web services  make people tend to think far ahead to discover new things on this technology. Increasing development and evolution of the various developments. Web service is one of media that suitable for system and platform communication, this service is considered as an efficient and effective  communication facility. Web service make a system communication  connected with Internet.The system is built with a proper analysis and  effective design to help human to communicate each other. The  design from start to end, is useful to help in writing the command of blogs which has a lot of comments. The  comments that belong to many website/blogs is recorder into one report so that make the review become easier. It also can  maximize the quality and the quantity of the website / blog.System is designed to facilitate the manager of the website/blog, especially in the pe-an-record comments entered. Manager of the website / blog just need to  provide a form which connected to the database as a means of data entry comments.